Endocrine Disruption of the Follicle-Stimulating Hormone Receptor Signaling During the Human Antral Follicle Growth - Roy, Neena; Mascolo, Elisa; Lazzaretti, Clara; Paradiso, Elia; D’Alessandro, Sara; Zaręba, Kornelia; Simoni, Manuela; Casarini, Livio (Frontiers in Endocrinology, 2021)
An increasing number of pollutants with endocrine disrupting potential are accumulating in the environment, increasing the exposure risk for humans. Several of them are known or suspected to interfere with endocrine signals, impairing reproductive functions. Follicle-stimulating hormone (FSH) is a glycoprotein playing an essential role in supporting antral follicle maturation and may be a target of disrupting chemicals (EDs) likely impacting female fertility. EDs may interfere with FSH-mediated signals at different levels, since they may modulate the mRNA or protein levels of both the hormone and its receptor (FSHR), perturb the functioning of partner membrane molecules, modify intracellular signal transduction pathways and gene expression. In vitro studies and animal models provided results helpful to understand ED modes of action and suggest that they could effectively play a role as molecules interfering with the female reproductive system. However, most of these data are potentially subjected to experimental limitations and need to be confirmed by long-term observations in human.